2016
DOI: 10.1101/048462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrotransposon proliferation coincident with the evolution of dioecy inAsparagus

Abstract: Current phylogenetic sampling reveals that dioecy and an XY sex chromosome pair evolved once, or possibly twice, in the genus Asparagus. Although there appear to be some lineage-specific polyploidization events, the base chromosome number of 2n = 2· = 20 is relatively conserved across the Asparagus genus. Regardless, dioecious species tend to have larger genomes than hermaphroditic species. Here, we test whether this genome size expansion in dioecious species is related to a polyploidization and subsequent chr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Transposable element diversity and composition can also be discerned through genome skim data. Although multiple studies have focused on the use of longer read technology such as 454 pyrosequencing (e.g., Harkess et al, 2016), the development of RepeatExplorer (Novák et al, 2013) and Transposome (Staton and Burke, 2015b) enable short reads to be used for transposon identification (e.g., Staton and Burke, 2015a). Using these approaches, genome skim data are able to provide novel insights into the evolution of nuclear genomes, not just organellar genomes.…”
Section: More Than Just Chloroplast Genomesmentioning
confidence: 99%
“…Transposable element diversity and composition can also be discerned through genome skim data. Although multiple studies have focused on the use of longer read technology such as 454 pyrosequencing (e.g., Harkess et al, 2016), the development of RepeatExplorer (Novák et al, 2013) and Transposome (Staton and Burke, 2015b) enable short reads to be used for transposon identification (e.g., Staton and Burke, 2015a). Using these approaches, genome skim data are able to provide novel insights into the evolution of nuclear genomes, not just organellar genomes.…”
Section: More Than Just Chloroplast Genomesmentioning
confidence: 99%
“…The hermaphroditic capacity of varietals is believed to be a heritable trait but this trait has yet to be mapped to any genomic coordinates. Sex chromosomes in flowering plants usually evolve from autosomes (Harkess et al 2016; Harkess et al 2017). Likewise, modern monoecious hemp varietals tend to decay into dioecious varietals with inbreeding but little is known about their chromosomal structures (Clarke 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The abundances of TEs in genomes have also been shown to be informative when inferring phylogenetic relationships among taxa, especially in groups rife with polyploidy, such as those in the Brassicales, because it adds an analysis complementary to species tree phylogenies (Dodsworth et al 2015;Harkess et al 2016;Dodsworth et al 2017;Vitales et al 2020). Several studies have used maximum parsimony methods to reconstruct phylogenetic trees, treating TE abundances as continuous characters (Dodsworth et al 2015;Dodsworth et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a study has shown the power of combining TE sequence similarity with TE abundance to understand evolutionary relationships (Vitales et al 2020). Generally, Copia and Gypsy are the most informative elements due to their high abundance in the genomes, whereas low-abundant TEs are insufficient to resolve the phylogenetic relations with these approaches (Dodsworth et al 2015;Harkess et al 2016;Dodsworth et al 2017;Vitales et al 2020).…”
Section: Introductionmentioning
confidence: 99%